Frontiers in photonics spotlight - Anvari, Bahman; Celebrano, Michele; De Angelis, Costantino; Huang, Shujuan; Poon, Ting-Chung; Richards, Bryce S.; Peccianti, Marco (Frontiers in Photonics, 2023)
Highlighting remarkable research output is an important mission of journals and scientists engaged in dissemination. With this spotlight-review we would like to provide visibility to some of the best recent research outputs and stress the pivotal role of their authors in the Photonics field.